ClipR-59 Interacts with Elmo2 and Modulates Myoblast Fusion - Sun, Yingmin (J Biol Chem, 2015)
Recent studies using ClipR-59 knock-out mice implicated this protein in the regulation of muscle function. In this report, we have examined the role of ClipR-59 in muscle differentiation and found that ClipR-59 knockdown in C2C12 cells suppressed myoblast fusion. To elucidate the molecular mechanism whereby ClipR-59 regulates myoblast fusion, we carried out a yeast two-hybrid screen using ClipR-59 as the bait and identified Elmo2, a member of the Engulfment and cell motility protein family, as a novel ClipR-59-associated protein. We showed that the interaction between ClipR-59 and Elmo2 was mediated by the atypical PH domain of Elmo2 and the Glu-Pro-rich domain of ClipR-59 and regulated by Rho-GTPase. We have examined the impact of ClipR-59 on Elmo2 downstream signaling and found that interaction of ClipR-59 with Elmo2 enhanced Rac1 activation. Collectively, our studies demonstrate that formation of an Elmo2·ClipR-59 complex plays an important role in myoblast fusion.